THE EXTRAVAGANCE AND LUXURY AMONG THE SELJUK SULTANS OF RUM AS DEPICTED IN THE CONCISE BOOK "SELJUKNAMA" AUTHORED BY AN ANONYMOUS WRITER. - Omer, Othman; Hussin, Ahlam (Humanities Journal of University of Zakho, 2025)
The Seljuk state of Rum (1) is one of the Islamic states that ruled Asia Minor for nearly two and a half centuries (470-704 AH / 1074-1307 AD), during which the sultans of the Sultanate were characterized by extravagance and luxury, as it generated huge sums of money from the conquests. They showed great generosity in bestowing gifts on the rulers. The parties and their messengers during their visits used to spend huge amounts of money on the leaders and princes during their victories and conquests of the Armenian castles and Byzantine cities. They also held celebrations, amusement, and mirth, in addition to the money and gifts they lavished on wedding occasions, etc. Therefore, this study sheds light on the phenomenon of extravagance and luxury practiced by the sultans of the Seljuks of Rum in Anatolia through the book “Mukhtasar Selcuknameh” by an unknown author, which is originally a summary of the book “Al-Awmār Al-Ala’i fi Al-Mār Al-Ala’ī” by Ibn Bibi.